Crushing performances of axially compressed woven kenaf fiber reinforced cylindrical composites - Ismail, Al Emran; Sadikin, Azmahani; Abdol Rahman, Mohd Nasrull; Mahzan, Shahruddin; Md. Salleh, Salihatun; Ahmad, Sufizar; Ridzuan, Mohd Baharudin (Penerbit UTHM, 2018)
This paper presents experimental investigations on the crushing performances of axially compressed woven kenaf fiber reinforced cylindrical composites. Based on the literature survey, there are tremendous amount of work are available on the crushing performances regardless whether the composite contained synthetic or natural fibers. However, lack number of work found in discussing the crushing capability for the composite tubes fabricated using woven kenaf mat reinforced composites. Kenaf fiber in the form of yarn is weaved into a woven mat before it is submerged into a resin bath prior the mats are shaped to form a cylindrical tube. There are two important parameters are used such as number of layers and fiber orientations. The composite tubes are then quasi-statically compressed to obtain the force-displacement curves. Energy absorption capability and other crashworthiness parameters are calculated and discussed in term of number of layers and fiber orientations. According to the results, it is found that both number of layer and fiber orientations played an important role in an elastic region or the first region. On the other hand, in the second stage, it is insignificantly affected the plateau stage where the curves seemed not much different.